When Policy Is Not Enough: Prospects And Challenges Of Artisanal And Small-Scale Mining In South Africa - Ledwaba, Pontsho; Nhlengetwa, Kgothatso (Journal of Sustainable Development Law and Policy, 2025)
As in most countries, artisanal and small-scale mining (ASM) activities are recognised in South Africa. ASM activities first became part of the socioeconomic development agenda of the country in 1994 after the change in government. ASM was identified as an important platform where disadvantaged South Africans can participate and benefit from the mining industry. This is because of the potential benefits that government has sought to support the sub-sector. In the past two decades, several programmes and initiatives have been introduced to promote and advance the sub-sector. In the majority of cases, these interventions failed to facilitate the development of the sub-sector and, to a large extent, its contribution to local economies. This is attributed to a myriad of challenges still facing the sub-sector today. The objective of this paper is to map all the critical developments that took place in the sub-sector in an attempt to develop and deploy appropriate assistance to the sub-sector. The paper assesses their impact, if any, on the growth of ASM in South Africa. With the country into its second decade of democracy, it has become crucial to reflect on past experiences and use them as learning curve to create a new thriving economy.